Intracerebral haemorrhage in patients taking different types of oral anticoagulants: a pooled individual patient data analysis from two national stroke registries - Siepen, Bernhard M; Forfang, Elisabeth; Branca, Mattia; Drop, Boudewijn; Mueller, Madlaine; Goeldlin, Martina B; Katan, Mira; Michel, Patrik; Cereda, Carlo; Medlin, Friedrich; Peters, Nils; Renaud, Susanne; et al. (Stroke and vascular neurology, 2024)
BackgroundWe investigated outcomes in patients with intracerebral haemorrhage (ICH) according to prior anticoagulation treatment with Vitamin K antagonists (VKAs), direct oral anticoagulants (DOACs) or no anticoagulation.MethodsThis is an individual patient data study combining two prospective national stroke registries from Switzerland and Norway (2013–2019). We included all consecutive patients with ICH from both registries. The main outcomes were favourable functional outcome (modified Rankin Scale 0–2) and mortality at 3 months.ResultsAmong 11 349 patients with ICH (mean age 73.6 years; 47.6% women), 1491 (13.1%) were taking VKAs and 1205 (10.6%) DOACs (95.2% factor Xa inhibitors). The median percentage of patients on prior anticoagulation was 23.7 (IQR 22.6–25.1) with VKAs decreasing (from 18.3% to 7.6%) and DOACs increasing (from 3.0% to 18.0%) over time. Prior VKA therapy (n=209 (22.3%); adjusted ORs (aOR), 0.64; 95% CI, 0.49 to 0.84) and prior DOAC therapy (n=184 (25.7%); aOR, 0.64; 95% CI, 0.47 to 0.87) were independently associated with lower odds of favourable outcome compared with patients without anticoagulation (n=2037 (38.8%)). Prior VKA therapy (n=720 (49.4%); aOR, 1.71; 95% CI, 1.41 to 2.08) and prior DOAC therapy (n=460 (39.7%); aOR, 1.28; 95% CI, 1.02 to 1.60) were independently associated with higher odds of mortality compared with patients without anticoagulation (n=2512 (30.2%)).ConclusionsThe spectrum of anticoagulation-associated ICH changed over time. Compared with patients without prior anticoagulation, prior VKA treatment and prior DOAC treatment were independently associated with lower odds of favourable outcome and higher odds of mortality at 3 months. Specific reversal agents unavailable during the study period might improve outcomes of DOAC-associated ICH in the future.